Daya Antibakteri Ekstrak Buah Adas (Foeniculum vulgare) Terhadap Bakteri Micrococcus luteus Secara In Vitro [Antibacterial Effort Of Adas Fruit (Foeniculum vulgare) Extract On Micrococcus luteus Bacterial By In Vitro] - Rahayu Kusdarwati; Ludira Sari; Sri Subekti (Faculty of Fisheries and Marine Universitas Airlangga, 2010)
AbstractOne of the disease attack of freshwater fish is micrococcus which caused by Micrococcus luteus bacterial. Antibiotic was caused of residual, polluted and expensive. Therefore, it was looked for alternative using natural and safety materials. The study used the fruit extract of adas as antibacterial to Micrococcus luteus. This experiment purpose to investigate of Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of fruit extract of adas to Micrococcus luteus. The study was done on 15 June-05 July 2009 on Development Center of Quarantine Fish Juanda; Institute Tropical Disease, Airlangga University Surabaya; and Department of Faculty Pharmacology of Medicine, Airlangga University Surabaya. The experiment was used experimental method which completely randomized design with twelve treatments and three replicates. The parameters observed were Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). The data analyzed used F test and was continued with Duncan's Multiple Range Test. The result indicated that fruit extract of adas had antibactericidal to Micrococcus luteus. According to inhibitory test growth of bacterial had inhibitory capacity (MIC) at concentration 1,56% (0,018 g/ml). Therefore, the bactericidal capacity (MBC) was at concentration 3,13% (0,036 g/ml).